Sustainable development as social equity: Policy contradictions and their impact on higher education - Monnapula-Mapesela, M (South African Journal of Higher Education, 2014)
Common discourse on sustainable development (SD) in higher education places emphasis on caring for, as well as protecting, the environment and natural resources. This conceptualisation negates the two other crucial pillars, namely, social equity and economic development. In South African higher education efforts for sustainable development are gaining popularity, although the focus is still on environmental sustainability. The thrust of this article is to analyse South African higher education policy for its pronouncement on SD in general and on social equity in particular. The article argues that although education underpins the success of SD, higher education policy shows minimal concern for SD. The article argues that SD found little space, if any, in the broad policy transformation agenda in 1994, yet it depends – and greatly so – on relevant, rigorous policy intervention and steering, not only for advocacy, but more importantly to curb the prevalence of factors that threaten sustainable education.
Published Article
Keywords: sustainable development; social equity; South African higher education; policy implications; transformation; sustainable education